AMPA receptor activation is rapidly toxic to cortical astrocytes when desensitization is blocked - David, JC (J Neurosci, 1996)
Although cultured astrocytes express functional glutamate receptors, they are generally resistant to excitotoxic cell death. We explored the role of receptor desensitization in glutamate-mediated astrocyte injury. In cultures of type 1 astrocytes from mouse neocortex, brief application of AMPA evoked small, rapidly desensitizing inward currents, whereas kainate evoked small, sustained currents. Neither agonist increased cytosolic calcium, and astrocyte toxicity occurred only after 24 hr exposure to high (500–1000 microM) concentrations of kainate but not to AMPA or glutamate. Cyclothiazide, a drug that selectively blocks AMPA receptor desensitization, greatly potentiated AMPA- or kainate-gated currents and intracellular calcium elevation. Coapplication of 10–100 microM cyclothiazide with glutamate, AMPA, or kainate produced widespread astrocyte cell death within 2 hr or application. The enhancement of toxicity by cyclothiazide, which alone was not toxic, was concentration-dependent for each of the tested agonists (EC50 30–100 microM) and was blocked by further addition of the selective AMPA/kainate antagonist 2,3-dioxo-6-nitro-7- sulfamoylbenzo(f)quinoxaline (NBQX). NMDA caused no injury even in the presence of cyclothiazide. Cyclothiazide-enhanced injury varied with the age of astrocyte cultures; the maximal effect occurred at approximately 2 weeks in vitro, and little death was seen after 4 weeks. Type 1 astrocytes express AMPA-type glutamate receptors that are unmasked by reducing their desensitization with cyclothiazide. Although overactivation of AMPA receptors can be rapidly lethal to astrocytes, rapid desensitization normally limits this toxicity. The extent of AMPA receptor desensitization may be an important determinant of glial vulnerability to excitotoxic insults.